2004
DOI: 10.1111/j.1365-2036.2004.01988.x
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori eradication decreases blood neutrophil and monocyte counts

Abstract: SUMMARYBackground: The effect of Helicobacter pylori infection on systemic disorders is not well understood. Aim: The purpose of this study was to elucidate the systemic effects of H. pylori infection by comparing differential counts of leukocytes and platelets in peripheral blood before and after eradication of H. pylori. Methods: A total of 164 H. pylori-positive patients underwent eradication therapy, and populations of peripheral blood leukocytes and platelets before and 0 (just after therapy), 1, 3 and 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 29 publications
2
9
2
Order By: Relevance
“…White blood cell, neutrophil, and lymphocyte counts have been reported to increase in H. pylori-infected patients [20,21]. In the present study, these counts were slightly higher in H. pylori-infected patients than in control subjects, and they decreased after eradication of H. pylori.…”
Section: Discussioncontrasting
confidence: 43%
“…White blood cell, neutrophil, and lymphocyte counts have been reported to increase in H. pylori-infected patients [20,21]. In the present study, these counts were slightly higher in H. pylori-infected patients than in control subjects, and they decreased after eradication of H. pylori.…”
Section: Discussioncontrasting
confidence: 43%
“…Kondo et al have analyzed peripheral blood mononuclear cell counts; specifically neutrophil and monocyte counts, in the peripheral blood of Hp (+) patients. They observed an increase in neutrophil and monocyte counts and therefore concluded that H. pylori infection plays a role in systemic disorders (23). Besides that, Karttunen et al observed a significant increase in peripheral blood basophiles in H. pylori patients (24).…”
Section: Discussionmentioning
confidence: 99%
“…Also, it was found in the eradicated group that neutrophils and monocytes counts were decreased significantly after eradication, with no significant change in eosinophils, basophils, and lymphocytes. On the other hand, there was no significant change in leucocytes in the noneradicated group 46 . These results were against the present study and may be due to different strains of the bacterium involved.…”
Section: Discussionmentioning
confidence: 70%